2009
DOI: 10.1187/cbe.09-07-0052
|View full text |Cite
|
Sign up to set email alerts
|

Non-STEM Undergraduates Become Enthusiastic Phage-Hunters

Abstract: To increase science literacy and appreciation among nonscience majors, we offered a course in which 20 non-STEM (science, technology, engineering, math) undergraduates participated in a unique, two-semester research experience. Each student isolated and characterized his or her own bacteriophage from soil samples. One bacteriophage was selected for sequencing and together, the class annotated the genome of the newly sequenced bacteriophage. The class produced a group poster and gave PowerPoint presentations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 6 publications
0
33
0
Order By: Relevance
“…This is especially true for CUREs implemented in nonvolunteer course contexts. Likewise, few studies have performed a comparative examination of these outcomes among STEM versus non-STEM students engaged in CUREs (e.g., Caruso et al , 2009). To address these concerns, we adopted a mixed-methods approach to broadly evaluate the implementation of a novel CURE in an introductory cell and molecular biology course, with specific assessment of the aforementioned cognitive and noncognitive outcomes conducted.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true for CUREs implemented in nonvolunteer course contexts. Likewise, few studies have performed a comparative examination of these outcomes among STEM versus non-STEM students engaged in CUREs (e.g., Caruso et al , 2009). To address these concerns, we adopted a mixed-methods approach to broadly evaluate the implementation of a novel CURE in an introductory cell and molecular biology course, with specific assessment of the aforementioned cognitive and noncognitive outcomes conducted.…”
Section: Discussionmentioning
confidence: 99%
“…With this information and a free program called VIGOR, students can identify all 12 viral proteins and perform bioinformatics analysis in comparison to ATCC reference strains [16]. In a sense, this laboratory is similar to the program sponsored by Howard Hughes Medical Institute called ''Phage-Hunters'' [17]. Studies have shown that the severity of experimental viral infections depends not only on the viral strain but also on the sleep and stress levels of the individuals involved [7][8][9][10].…”
Section: Sequencingmentioning
confidence: 99%
“…Microbes are ubiquitous in the environment and have countless positive and negative influences on society. This relevance can be seen in the wide variety of published microbiology lab modules including those with medical (7,20), environmental (3,16), and food processing (19,22) themes. A number of these cited experiments are also discoverydriven, in that they have an unknown outcome, allowing students to participate in the scientific method.…”
Section: Introductionmentioning
confidence: 99%